Pengembangan Bahan Ajar Asesmen dan Evaluasi Pembelajaran Bahasa Indonesia pada Aspek Keterampilan Berbicara Berbantuan Edpuzzle - Ika Febriana; Nurul Azizah; Rosmaini (sarasvati, 2026)
This study is driven by the limited availability of instructional materials for the course on Assessment and Evaluation of Indonesian Language Learning, particularly in speaking skills. Students require relevant and adequate resources to support their learning, as the competencies gained from this course will be applied in their future profession, especially in teaching. However, the lack of comprehensive and technology-integrated materials has become a challenge for both lecturers and students in the Indonesian Language and Literature Education Program, Faculty of Languages and Arts (FBS), Universitas Negeri Medan. In addition, such materials are also needed by Indonesian language teachers at the junior and senior high school levels to support effective classroom assessment practices. To address these issues, this study aims to develop instructional materials assisted by Edpuzzle as an innovative solution to overcome existing limitations. The purpose of this study is to: (1) describe the process of developing instructional materials for the Assessment and Evaluation of Indonesian Language Learning in the area of speaking skills using Edpuzzle, and (2) examine the feasibility (validity) of these instructional materials, based on expert validation, practitioner assessment, and student responses, when implemented in the Indonesian Language Education and Literature Program, Faculty of Languages and Arts, Medan State University. This research employs a Research and Development (R&D) method, consisting of stages such as needs analysis, resource identification, product design, development, validation, testing, and finalization. Through these stages, the study is expected to produce valid and feasible instructional materials.